Attityder till implementering av precisionsodlingsteknik - Olsson, Frida (2008)
Different techniques for precision agriculture have been available during the last decade. Some of them are more widely used than others. The main purpose of this thesis was to investigate the different attitudes to precision agriculture that exists among farmers and advisors in Sweden.